Myoid hamartoma breast with pseudo angiomatous stromal hyperplasia: a case report and review of literature - G., Ravikumar; T., Sivakami; GR, Sugapradha (International Surgery Journal, 2016)
Hamartomas of the breast, also known as fibroadenolipomas, lipofibroadenomas or adenolipomas are benign lesions with low risk of recurrences. Hamartomas account for between 0.04 and 1.15% of all benign breast tumours in females. Myoid hamartoma of the breast (MHB) with Pseudo Angiomatous Stromal Hyperplasia (PASH) is an extremely rare lesion. These cases will be misdiagnosed preoperatively. Histopathology only gives definitive diagnosis. Sixteen year old girl admitted with a mass of two months duration in the left breast in which reduction mammoplasty was done two years back. Ultra sonogram of the left breast revealed a well circumscribed 10cm x 6 cm x 3cm mass with echogenic and isoechoic areas. A core needle biopsy was done and reported as fibro adenoma of the left breast. Excision of the mass with adequate margins was done. The histopathology report of the resected mass showed myoid hamartoma breast with pseudo angiomatous stromal hyperplasia (PASH). So far there is no literature report about myoid hamartoma breast with pseudo angiomatous stromal hyperplasia (PASH) in an already reduction mammoplasty done patient. We present this case for its rarity and also to stress the importance of immunohistochemical studies in benign breast lesions.